Trace Level Detection of Bisphenol A Analogues and Parabens by LC-MS/MS in Human Plasma from Malaysians - Wiraagni, Idha Arfianti; Mohd, Mustafa Ali; Rashid, Rusdi Abdul; Haron, Didi Erwandi Mohamad (Hindawi Publishing Corporation, 2020)
In this study, a novel LC-MS/MS method was designed using a simple extraction procedure that was scientifically developed to capture the most relevant bisphenol A (BPA) analogues (BPB, BPF, BPS, and BPAF) and parabens (propylparaben, ethylparaben, butylparaben, and methylparaben) in human plasma. The LC-MS/MS method was validated using US FDA guidelines, and all validation requirements were satisfactory. This is the method that allows for the detection of plasma bisphenols and parabens in one run and is also the fastest BPA analogue and paraben detection technique for human plasma. The method was used to analyze samples from 150 healthy volunteers from Malaysia who enrolled in the study. No BPB was detected in any of the volunteers; however, 99.3% were positive for BPF. Only 24% and 10.7% of volunteers were positive for BPAF and BPS, respectively. A high percentage of volunteers were negative for propylparaben, ethylparaben, butylparaben, and methylparaben (56%, 68%, 86.7%, and 83.3%, respectively). These results suggest that persons in Malaysia are exposed to different BPA analogues and parabens, from both the daily use of products (cosmetic and plastic products) and the environment. © 2020 Idha Arfianti Wiraagni et al.